Prevalence of Trachoma in Kano State, Nigeria: Results of 44 Local Government Area-Level Surveys. (4th May 2017) - Mpyet, Caleb; Muhammad, Nasiru; Adamu, Mohammed Dantani; Muazu, Habila; Umar, Murtala Muhammad; Goyol, Musa; Yahaya, Hadi Bala; Onyebuchi, Uwazoeke; Ogoshi, Chris; Hussaini, Tijjani; Isiyaku, Sunday; William, Adamani; et al.
ABSTRACT: Purpose : We sought to determine the prevalence of trachoma in 44 Local Government Areas (LGAs) of Kano State, Nigeria. Methods : A population-based prevalence survey was conducted in each Kano LGA. We used a two-stage systematic and quasi-random sampling strategy to select 25 households from each of 25 clusters in each LGA. All consenting household residents aged 1 year and above were examined for trachomatous inflammation–follicular (TF), trachomatous inflammation–intense (TI) and trichiasis. Results : State-wide crude prevalence of TF in persons aged 1–9 years was 3.4% (95% CI 3.3–3.5%), and of trichiasis in those aged ≥15 years was 2.3% (95% CI 2.1–2.4%). LGA-level age- and sex-adjusted trichiasis prevalence in those aged ≥15 years ranged from 0.1% to 2.9%. All but 4 (9%) of 44 LGAs had trichiasis prevalences in adults above the elimination threshold of 0.2%. State-wide prevalence of trichiasis in adult women was significantly higher than in adult men (2.6% vs 1.8%; OR = 1.5, 95% CI 1.3–1.7; p = 0.001). Four of 44 LGAs had TF prevalences in 1–9-year-olds between 10 and 15%, while another six LGAs had TF prevalences between 5 and 9.9%. In 37 LGAs, >80% of households had access to water within 30 minutes round-trip, but household latrine access was >80% in only 19 LGAs. Conclusion : Trichiasis is a public health problem in most LGAs in Kano. Surgeons need to be trained and deployed to provide community-based trichiasis surgery, with emphasis on delivery of such services to women. Antibiotics, facial cleanliness and environmental improvement are needed in 10 LGAs.